Digital Banking Transformation and Community Financial Inclusion: A Literature Review of Fintech’s Role in Empowering Emerging Economies - Aripin, Zaenal (Yayasan Kreatif Indonesia Emas, 2024)
This literature review meticulously explores the intricate intersection between the digital transformation of banking and the advancement of community financial inclusion in emerging economies. It systematically analyzes how a diverse range of fintech innovations, such as mobile wallets, digital lending platforms, and branchless banking models, are being leveraged to promote more inclusive financial ecosystems. The review identifies and synthesizes the opportunities and key challenges, as well as the critical success factors that govern the efficacy of digital banking initiatives within marginalized communities. Furthermore, the study delves into the socio-cultural, economic, and policy environments that critically shape the adoption and long-term impact of digital financial inclusion efforts. By drawing upon a wide range of academic research and institutional reports, this paper offers a comprehensive and integrated perspective on how technology can be harnessed responsibly to empower emerging economies and foster more equitable access to financial services.